A qualitative exploration of the experience of Black women in violent relationships - Mesatywa, Nontando Jennifer (Rhodes University, Faculty of Humanities, Department of Social Work)
This study is a qualitative exploration of black women experiences in violent relationships. The study was conducted at Masimanyane Women Support Centre in East London. As a qualitative exploratory study, in-depth interviews were conducted and a sample of ten abused women was utilized. A study of related literature has been made to focus on the existing literature concerning abuse on black women. Various theories have been explored, various feminist views were discussed and the existing legal system, nationally and internationally was looked into. The findings suggest that black women are abused by their partners. Alcohol abuse, failing to support the children and extra marital relationships have been cited as some of the reasons. Women in abusive relationships in this study sustained physical as well as emotional abuse. The professional networks assisted these women to some extent. However, there is an indication of a dire need for training, interdisciplinary approach and a legal system that prohibits further abuse by male partners. Various recommendations have been postulated. The researcher indicated that there is a need for empowering programs for the abused, rehabilitative program for the abuser, and an effective legal system to prevent further abuse on women.
Keywords: Abused women -- South Africa; Abused wives -- South Africa; Family violence -- Research -- South Africa